2020
DOI: 10.1007/s10549-020-05782-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of palbociclib plus endocrine therapy by prognostic and intrinsic subtype and biomarker analysis in patients with bone-only disease: a joint analysis of PALOMA-2 and PALOMA-3 clinical trials

Abstract: Purpose This analysis evaluated the relationship between treatment-free interval (TFI, in PALOMA-2)/disease-free interval (DFI, in PALOMA-3) and progression-free survival (PFS) and overall survival (OS, in PALOMA-3), treatment effect in patients with bone-only disease, and whether intrinsic subtype affects PFS in patients receiving palbociclib. Methods Data were from phase 3, randomized PALOMA-2 and PALOMA-3 clinical studies of hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 38 publications
(89 reference statements)
0
42
0
Order By: Relevance
“… Potential resistance biomarkers from tumor analyses of primary tumor or metastases in patients with HR+ve mBC (n = 1,162; Molecular alterations associated with drug resistance [solid tumors: DNA, RNA, or protein]). Intrinsic and acquired resistance biomarkers from PALOMA2 (n = 454 palbociclib plus letrozole), 29 PALOMA3 (gene expression analyses n = 302 paired samples; palbociclib plus fulvestrant), 30 the study by Wander et al 22 (n = 58; paired samples CDK4/6i plus endocrine therapy), and the study by Li et al 21 for FAT1 loss (CDK4/6i plus endocrine therapy; n = 348). AURKA , aurora kinase A; CDK4/6, cyclin-dependent kinase 4 and 6; EGFR, epidermal growth factor receptor; ER, estrogen receptor; FAT1 , FAT atypical cadherin 1; FGFR2 , fibroblast growth factor receptor 2; HER2 , human epidermal growth factor receptor 2; IGFR1, insulin-like growth factor 1 receptor; MET, mesenchymal-epithelial transition factor; PLK, polo-like kinase; RAS, rat sarcoma virus; RB1 , Retinoblastoma 1 gene.…”
Section: Resultsmentioning
confidence: 99%
“… Potential resistance biomarkers from tumor analyses of primary tumor or metastases in patients with HR+ve mBC (n = 1,162; Molecular alterations associated with drug resistance [solid tumors: DNA, RNA, or protein]). Intrinsic and acquired resistance biomarkers from PALOMA2 (n = 454 palbociclib plus letrozole), 29 PALOMA3 (gene expression analyses n = 302 paired samples; palbociclib plus fulvestrant), 30 the study by Wander et al 22 (n = 58; paired samples CDK4/6i plus endocrine therapy), and the study by Li et al 21 for FAT1 loss (CDK4/6i plus endocrine therapy; n = 348). AURKA , aurora kinase A; CDK4/6, cyclin-dependent kinase 4 and 6; EGFR, epidermal growth factor receptor; ER, estrogen receptor; FAT1 , FAT atypical cadherin 1; FGFR2 , fibroblast growth factor receptor 2; HER2 , human epidermal growth factor receptor 2; IGFR1, insulin-like growth factor 1 receptor; MET, mesenchymal-epithelial transition factor; PLK, polo-like kinase; RAS, rat sarcoma virus; RB1 , Retinoblastoma 1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…35,[39][40][41] Subpopulation treatment effect pattern plot (STEPP) analysis presented at the 2018 American Society of Clinical Oncology Annual Meeting showed that the treatment effect of the addition of palbociclib to endocrine therapy was not impacted by the length of the initial treatment-free interval (TFI; PALOMA-2) or disease-free interval (DFI; PALOMA-3). 43 The median TFI in PALOMA-2 was 37.1 months for palbociclib plus letrozole and 30.9 months for letrozole plus placebo, with approximately 56% of patients having a TFI of over 2 years. 43 The median DFI in PALOMA-3 was 49.2 months for palbociclib plus fulvestrant versus 52.0 months for fulvestrant plus placebo, with over 80% of patients having had a DFI more than 2 years.…”
Section: Efficacymentioning
confidence: 96%
“…43 The median TFI in PALOMA-2 was 37.1 months for palbociclib plus letrozole and 30.9 months for letrozole plus placebo, with approximately 56% of patients having a TFI of over 2 years. 43 The median DFI in PALOMA-3 was 49.2 months for palbociclib plus fulvestrant versus 52.0 months for fulvestrant plus placebo, with over 80% of patients having had a DFI more than 2 years. 43 In addition, patient subgroup analyses of PALOMA-2 showed patients with either a low disease burden or a demonstrated sensitivity to endocrine monotherapy derived substantial PFS benefit from the combination of palbociclib plus letrozole (i.e.…”
Section: Efficacymentioning
confidence: 96%
“…However, data suggest that some subgroups of patients have a higher benefit than others, mainly in the subgroups of postmenopausal women, patients with visceral metastasis, and patients with the progression of disease under endocrine therapy (second-line therapy) [ 29 ]. Regarding the intrinsic molecular subtypes of BC, PFS is marginally pronounced in the luminal A subtype compared to the luminal B subtype in the cohort of PALOMA-2 and -3 [ 30 ].…”
Section: Clinical Impact and Real-life Data On Cdk4/6 Inhibitorsmentioning
confidence: 99%